Development Of Absorption Capability Attributes For Technology Transfer Performance: A Pilot Study In National Automotive Industry - Siti Aishah, Md Hassan; Ahmad, Othman (2011)
Technology transfer is one of the strategies to obtain advanced technology in order to enhance technological development. Malaysia has shown its positive progress in technology transfer through a steady trend by bringing in advanced technology into the country especially during the past two decades. Although there have been many empirical studies regarding the key success factors of technology transfer performance, firm absorption capabilities is seldom discussed. In practice, the technology transfer will not be successfully achieved if technology absorption capabilities are not taken seriously. Therefore, this study was conducted to investigate the relationship between absorption capability attributes; employee capability, knowledge sharing, working culture, R&D capability and communication capability with technology transfer performance. These five attributes/variables were developed based on the Malaysian Government Reports. The pilot study was conducted by using questionnaire surveys which were distributed to national automotive companies. The pilot results were analyzed using Statistical Process for Social Science (SPSS) software. The result found that the cronbach’s alpha values for all variables were greater than 0.6 and thus accepted. In conclusion, by presenting this new development of absorption capability variables, the real data could be proceeded to be collected. However, in-depth analysis needs to be carried out to confirm the validation of the instruments used.